La identidad mexicana en libros escolares y narrativas Un enfoque crítico y sociocognitivo - Nalleli García Agüero, Alba (De Gruyter, 2021)
This study analyzes the discursive construction strategies that structured the cognitive model of Mexican national identity in four generations of textbooks (1960-2009). Using tools from the fields of Cognitive Linguistics and Critical Discourse Studies, the sociocognitive analysis is completed by a social-interactional empirical study drawing on the theoretical and methodological framework of Narrative Studies.